THE ROLE OF CLOUD TECHNOLOGIES IN THE DIGITALIZATION OF EDUCATION - Muhammadiev Feruz Gafurjonovich (Scholar Express Journals, 2023)
This article is devoted to the implementation of the competence-based approach in the training of future teachers of foreign languages. It is due to the accelerating world processes of globalization and informatization. The concept of professional competence of a teacher is a unity of theoretical and practical training in the general structure of a person and characterizes his professional skills.
Keywords: competence; sociocultural competence; competence approach